2011
DOI: 10.1002/adsc.201100431
|View full text |Cite
|
Sign up to set email alerts
|

Construction of 1,2,5‐Tricarbonyl Compounds using Methyl Cyanoacetate as a Glyoxylate Anion Synthon Combined with Copper(I) Iodide‐Catalyzed Aerobic Oxidation

Abstract: A practical and efficient synthesis of various 1,2,5-tricarbonyl compounds is described. The synthesis has been carried out by a conjugate addition of methyl cyanoacetate to the b-position of a,b-unsaturated carbonyl compounds and a subsequent copper(I) iodide-catalyzed aerobic oxidation. In addition, various a-aryl-and a-alkyl-a-keto esters have been synthesized using a similar approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Indirect methods for the preparation of the requisite α,δ-diketo esters 5 have been reported by us 10b and others, 36 but the most direct and atom economical approach to these substrates would be a new Stetter reaction between commercial ethyl glyoxylate and α,β-enones. 37 This reaction was previously reported to be unsuccessful with thiazolium carbenes, 36c but we have found that effective catalysis can be realized by employing the Rovis triazolium carbene derived from salt 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Indirect methods for the preparation of the requisite α,δ-diketo esters 5 have been reported by us 10b and others, 36 but the most direct and atom economical approach to these substrates would be a new Stetter reaction between commercial ethyl glyoxylate and α,β-enones. 37 This reaction was previously reported to be unsuccessful with thiazolium carbenes, 36c but we have found that effective catalysis can be realized by employing the Rovis triazolium carbene derived from salt 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of methyl 3-fluoro-4-nitrobenzoate ( 8 ) with methyl 2-cyanoacetate under basic conditions delivered intermediate 9 . 12 Subsequent copper(I) iodide-catalyzed aerobic oxidation 12 delivered methyl 2-oxo-2-phenylacetate 10 , and from here, target 1a was prepared in parallel to the chemistry employed in Scheme 1. With 1a in hand, saponification and nitro reduction were accomplished as outlined in Scheme 3 to deliver analogs 1b , 1j , and 1k .…”
Section: Resultsmentioning
confidence: 99%
“…1 The protocol is a very simple and high-yielding process of 2,5-diketoesters (vide infra, Scheme 1).…”
Section: Introductionmentioning
confidence: 99%